2009
DOI: 10.1002/bies.200800191
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenicity in the tubercle bacillus: molecular and evolutionary determinants

Abstract: In contrast to the great majority of mycobacterial species that are harmless saprophytes, Mycobacterium tuberculosis and other closely related tubercle bacilli have evolved to be among the most important human and animal pathogens. The need to develop new strategies in the fight against tuberculosis (TB) and related diseases has fuelled research into the evolutionary success of the M. tuberculosis complex members. Amongst the various disciplines, genomics and functional genomics have been instrumental in impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2009
2009
2025
2025

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 77 publications
0
34
0
Order By: Relevance
“…The toxic CTD of CpnT challenges the paradigm that M. tuberculosis is one of the few bacterial pathogens that does not produce toxins (2). Based on our results, we propose the following model for the biological function of CpnT (Fig.…”
Section: Discussionmentioning
confidence: 80%
“…The toxic CTD of CpnT challenges the paradigm that M. tuberculosis is one of the few bacterial pathogens that does not produce toxins (2). Based on our results, we propose the following model for the biological function of CpnT (Fig.…”
Section: Discussionmentioning
confidence: 80%
“…The in-depth analysis of this enormous dataset will allow specific traits linked to pathogenicity, transmissibility, and/or other strain-or strain-lineage-specific particularities to be identified that have likely been selected during mycobacterial evolution. (49). Whole-genome comparisons of M. tuberculosis with five selected mycobacterial species such as M. avium paratuberculosis (50), M. leprae (11), M. marinum (15), Mycobacterium smegmatis (GenBank accession-no.…”
Section: Mycobacterial Genomicsmentioning
confidence: 99%
“…Whole-genome comparisons of M. tuberculosis with five selected mycobacterial species such as M. avium paratuberculosis (50), M. leprae (11), M. marinum (15), Mycobacterium smegmatis (GenBank accession-no. NC_008596), and M. ulcerans (13), for example, revealed 1,072 orthologous genes that are conserved across the six species tested, thus potentially defining the minimum mycobacterial genome (15,49). Sequence comparisons of the core genes among these strains showed that M. tuberculosis is most closely related to M. marinum and least closely related to the environmental saprophyte M. smegmatis (15), which is in agreement with previous results from partial sequence analysis of the 16S rDNA (5).…”
Section: Mycobacterial Genomicsmentioning
confidence: 99%
“…Although extant strains of "M. canettii" still cause human tuberculosis, they differ significantly in infectivity and appear to be relatively ancestral [85,86]. Genomic studies indicate that the very diverse "M. canettii" isolates appear to coalesce into a form of bottleneck after which all the modern human and animal biotypes evolved in a relatively linear manner [83,84,87,88]. A plausible working hypothesis for the evolution of M. tuberculosis sensu stricto is outlined in Figure 11, highlighting the possible contribution of cell envelope lipid composition.…”
Section: Evolutionary and Pathogenicity Aspects Of Cell Envelope Compmentioning
confidence: 99%